Will personality traits affect the use of e-cigar among college students? A cross-sectional study in Guangdong Province, China - Mai, Jianrong; Lin, Lina; Zhou, Ling; Guan, Qinyi; Zhu, Wenhui; Zhou, Wenzan (Frontiers in Public Health, 2022)
Background The prevalence of e-cigar among adolescents and young adults around the world is increasing rapidly, which has a serious impact on the health of young people. This study assessed the prevalence of e-cigar among college students and to explore the relationship between e-cigar use and personality traits. Methods This study conducted an electronic questionnaire survey on college students who were from three undergraduate universities and three junior colleges in Guangdong Province from January 2022 to March 2022. The survey was conducted by stratified cluster sampling, and the respondents were 1362. Statistical descriptions are used to describe the demographic characteristics and personality traits of participants. Mann-Whitney U tests, and Chi-square tests were used to compare the differences between current e-cigar users and non e-cigar users. Two-step hierarchical Logistic regression was used to predict the associated factors with e-cigar use. Results The prevalence of current e-cigar users was 5.1%. Agreeableness showed statistically significant higher in non-users (Z = 2.585, P < 0.01). Moreover, gender (AOR = 0.312, 95%CI: 0.174–0.562), the relationship with mother (AOR = 5.887, 95%CI: 1.460–23.748), friends who use e-cigar (AOR = 3.808, 95%CI: 2.159–6.719), allowance per month (AOR = 2.482, 95%CI: 1.371–4.490), and agreeableness (AOR = 0.957, 95%CI: 0.918–0.997) were related to the use of e-cigar. Conclusion The level of agreeableness is associated with the use of e-cigar among college students. All these provided an important theoretical basis for future intervention.